Female soccer knee injury: Observed knowledge gaps in injury prevention among players/parents/coaches and current evidence (the KNOW study) - Orr, B.; Brown, C.; Hemsing, J.; McCormick, T.; Pound, S.; Otto, D.; Emery, C. A.; Beaupre, L. A. (Scandinavian Journal of Medicine & Science in Sports, 2013)
This study sought to determine if knowledge regarding the risk for knee injuries and the potential for their prevention is being translated to female adolescent soccer players (13-18 years), their parents, and coaches. Eligible participants in the 2007 indoor soccer season were surveyed to determine their knowledge of the risk for and the potential to prevent knee injuries, and their knowledge of effective prevention strategies, if they felt that injury prevention was possible. Team selection was stratified to be representative of both competitive and recreational level play and age group distributions within the selected soccer association. Of the study subjects, 773/1396 (55.4%) responded to the survey: 408 (53%) players, 292 (38%) parents, and 73 (9%) coaches. Most respondents (538 [71%]) were aware of the risk for knee injury. Coaches and parents were more likely than players to view knee injuries as preventable; however, appropriate prevention strategies were often not identified. Four hundred eighty-four (63.8%) respondents reported that they had never received information on knee injuries. Substantial knowledge gaps regarding knee injury prevention and effective preventative strategies were identified. Given the predominance of knee injuries in female adolescent soccer players, there is an urgent need for knowledge translation of prevention strategies to decrease both incidence and long-term consequences of knee injuries.